Strategi Inovatif Dalam Pelatihan Analisis Pekerjaan: Mengatasi Tantangan, Memaksimalkan Sumber Daya, dan Mengadaptasi Tren Global di Era Digital - Ranyla Putri Amelliya; Riya Agustina Kusairi; Iriani Ismail (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the digital era, training for job analysis faces various complex challenges, such as limited technological infrastructure, resistance to change, lack of digital competence, and budget constraints. This study explores these challenges while offering strategic solutions to enhance the effectiveness of training in job analysis. Proposed solutions include adopting technologies such as Learning Management Systems (LMS), gamification-based training, and collaboration with professional training providers. Additionally, change management focused on educating employees about the importance of digital training is highlighted as a critical factor. This study emphasizes the transformation of training methods from traditional to digital, the benefits of technology in training, and practical strategies to overcome implementation barriers. By leveraging technology-driven approaches, organizations can improve the quality of job analysis while fostering a more adaptive workforce in the digital era.